PENGEMBANGAN KOMIK DIGITAL BERBANTUAN CANVA BERBASIS GUIDED INQUIRY PADA MATERI SISTEM REPRODUKSI UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS XI MAN 1 JEMBER - Umiyatul Mabruroh; Nanda Eska Anugrah Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop and determine the validity, practicality, and effectiveness of a Canva-assisted digital comic based on Guided Inquiry as a biology learning medium for Grade XI students at MAN 1 Jember. This study employed a Research and Development (R&D) approach using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews, observations, expert validation, student response questionnaires, and learning outcome tests (pretest–posttest). Data were analyzed using percentage analysis, the Wilcoxon Signed Rank Test, and N-Gain analysis. The results showed that the developed media achieved an average validity score of 94.04% categorized as highly valid, a practicality score of 88.16% categorized as highly practical, and effectiveness results indicating improvement in students’ learning outcomes with an N-Gain score of 0.85 (highly effective category). The Wilcoxon test also showed a significance value of 0.000 (<0.05), indicating a significant difference between learning outcomes before and after media implementation. Therefore, the Canva-assisted digital comic based on Guided Inquiry is feasible and effective to be implemented as a biology learning medium.